BOOK REVIEWS. Issue 4 (1st September 2013) - Unknown
Abstract : Books reviewed in this issue Literature and Fine Arts Khapaeva, Dina. Nightmare: From Literary Experiments to Cultural Project . Russian History and Culture, Vol. 10. Bagshaw, Hilary B. P. Religion in the Thought of Mikhail Bakhtin: Reason and Faith . Ashgate New Critical Thinking in Religion, Theology and Biblical Studies Series. Depretto, Catherine, ed. Un autre Tolstoï . Beretta, Cristina. Das erotische Unbehagen in der russischen Literatur um 1900: Subversive Entsagung von Arthur Schopenhauer über Lev Tolstoj und Vladimir Solov'ev zu Fedor Sologub . Kalb, Judith E. Russia's Rome: Imperial Visions, Messianic Dreams, 1890–1940 . Rubin, Dominic. The Life and Thought of Lev Karsavin: "Strength made perfect in weakness …". Sicher, Efraim. Babel' in Context: A Study in Cultural Identity . Borderlines: Russian and East European Jewish Studies. Ivashkin, Alexander, and Andrew Kirkman, eds. Contemplating Shostakovich: Life, Music and Film . Rofe, Michael. Dimensions of Energy in Shostakovich's Symphonies . Kleberg, Lars, and Aleksei Semenenko, eds. Aksenov and the Environs . Maguire, Muireann. Stalin's Ghosts: Gothic Themes in Early Soviet Literature . Russian Transformations: Literature, Thought, Culture 4. Lalo, Alexei, trans. and ed. The Birth of the Body: Russian Erotic Prose of the First Half of the Twentieth Century: A Reader . Russian History & Culture. Hägglund, Martin. Dying for Time: Proust, Woolf, Nabokov . Norman, Will. Nabokov, History and the Texture of Time . Glazov‐Corrigan, Elena. Art after Philosophy: Boris Pasternak's Early Prose . Pontieri, Laura. Soviet Animation and the Thaw of the 1960s: Not Only for Children . Brintlinger, Angela. Chapaev and His Comrades: War and the Russian Literary Hero across the Twentieth Century . Cultural Revolutions: Russia in the Twentieth Century. Banerjee, Anindita. We Modern People: Science Fiction and the Making of Russian Modernity . History Uspenskij, Boris, and Victor Zhivov. " Tsar and God" and Other Essays in Russian Cultural Semiotics . Edited by Marcus C. Levitt. Ars Rossica. Vishlenkova, E., R. Galiullina, and K. Il'ina. Russkie professora: Universitetskaia korporativnost' ili professional'naia solidarnost '. Drozdov, Iu. N. Tiurkskoiazychnyi period evropeiskoi istorii . Schippan, Michael. Die Aufklärung in Russland im 18. Jahrhundert . Rey, Marie‐Pierre. Alexander I: The Tsar who Defeated Napoleon . Translated by Susan Emanuel. Antonova, Katherine Pickering. An Ordinary Marriage: The World of a Gentry Family in Provincial Russia . Kuxhausen, Anna. From the Womb to the Body Politic: Raising the Nation in Enlightenment Russia . Wirtschafter, Elise Kimerling. Religion and Enlightenment in Catherinian Russia: The Teachings of Metropolitan Platon . Leonhard, Jörn and Ulrike von Hirschhausen, eds. Comparing Empires: Encounters and Transfers in the Long Nineteenth Century . McReynolds, Louise. Murder Most Russian: True Crime and Punishment in Late Imperial Russia . Tanny, Jarrod. City of Rogues and Schnorrers: Russia's Jews and the Myth of Old Odessa . Miller, Burton Richard. Rural Unrest during the First Russian Revolution: Kursk Province, 1905–1906 . Historical Studies in Eastern Europe and Eurasia. Bilenky, Serhiy. Romantic Nationalism in Eastern Europe: Russian, Polish, and Ukrainian Political Imaginations . Kantor, Iuliia, and Mariush Volos. Treugol'nik Moskva – Varshava – Berlin: Ocherki istorii sovetsko‐pol'sko‐germanskikh otnoshenii v 1918–1939 gg . Glantz, David M. Barbarossa Derailed: The Battle for Smolensk 10 July–10 September 1941 . 2 vols. Wanner, Catherine, ed. State Secularism and Lived Religion in Soviet Russia and Ukraine . Chatterjee, Choi, and Beth Holmgren, eds. Americans Experience Russia: Encountering the Enigma, 1917 to the Present . Routledge Studies in Cultural History. Saul, Norman E. The Life and Times of Charles R. Crane, 1858–1939: American Businessman, Philanthropist, and a Founder of Russian Studies in America . Miller, Matthew Lee. The American YMCA and Russian Culture: The Preservation and Expansion of Orthodox Christianity, 1900–1940 . Landau, Julia Franziska. Wir bauen den großen Kuzbass! Bergarbeiteralltag im Stalinismus 1921–1941 . Neireck, Miriam. When Pigs Could Fly and Bears Could Dance: A History of the Soviet Circus . Harris, Steven E. Communism on Tomorrow Street: Mass Housing and Everyday Life after Stalin . Brown, Kate. Plutopia: Nuclear Families, Atomic Cities, and the Great Soviet and American Plutonium Disasters . Reisch, Alfred A. Hot Books in the Cold War: The CIA‐Funded Secret Western Book Distribution Program behind the Iron Curtain . Davis, Donald E., and Eugene P. Trani. The Reporter Who Knew Too Much: Harrison Salisbury and the New York Times. Etkind, Alexander. Warped Mourning: Stories of the Undead in the Land of the Unburied . Cultural Memory in the Present. Klumbytë, Neringa, and Gulnaz Sharafutdinova, eds. Soviet Society in the Era of Late Socialism, 1964–1985 . Jones, Stephen. Georgia: A Political History since Independence . Social Sciences, Contemporary Russia, and Other Batalden, Stephen K. Russian Bible Wars: Modern Scriptural Translation and Cultural Authority . Belova, Eugenia, and Valery Lazarev. Funding Loyalty: The Economics of the Communist Party . The Yale‐Hoover Series on Stalin, Stalinism, and the Cold War. Shorten, Richard. Modernism and Totalitarianism: Rethinking the Intellectual Sources of Nazism and Stalinism, 1945–Present . Bassin, Mark, and Catriona Kelly, eds. Soviet and Post‐Soviet Identities . Mijnssen, Ivo. The Quest for an Ideal Youth in Putin's Russia I: Back to Our Future! History, Modernity and Patriotism According to Nashi, 2005–2012 . Soviet and Post‐Soviet Politics and Society. Lassila, Jussi. The Quest for an Ideal Youth in Putin's Russia II: The Search for Distinctive Conformism in the Political Communication of Nashi, 2005–2009 . Soviet and Post‐Soviet Politics and Society. Chebankova, Elena. Civil Society in Putin's Russia . BASEES/Routledge Series on Russian and European Studies.